Properties of a Putative Cambialistic Superoxide Dismutase from the Aerotolerant Bacterium Streptococcus thermophilus Strain LMG 18311 - De Vendittis, Alberto; Marco, Salvatore; Di Maro, Antimo; Chambery, Angela; Albino, Antonella; Masullo, Mariorosario; Michniewicz, Andzelika; Parlato, Giuseppe; De Angelis, Amalia; De Vendittis, Emmanuele; Rullo, Rosario (Protein and Peptide Letters, 2012)
The aerotolerance of the lactic-fermentative bacterium Streptococcus thermophilus is mainly based on the key antioxidant function of superoxide dismutase (StSOD). In this work, the comparison of recombinant StSOD (rStSOD) forms obtained from two different initiation triplets indicated that the enzyme from S. thermophilus strain LMG 18311 spans 201 residues. rStSOD is organised as a homodimer, even though protein aggregates are formed in concentrated solutions. The capability of binding and exchanging Fe or Mn in the active site classifies rStSOD as a putative cambialistic enzyme; the moderate preference for iron is counteracted by a 1.5-fold higher activity measured for the Mn-containing form. The enzyme is thermostable, being its half-inactivation time 10 min at 73.5°C; the energetic parameters of the heat inactivation process are regulated by the level of Mn cofactor. The effect of Mn content on the rStSOD sensitivity towards inhibitors and inactivators was also evaluated. Sodium azide acts as a weak inhibitor of rStSOD and its Mn content does not greatly affect this sensitivity. Concerning the physiological inactivator hydrogen peroxide, the Mn-enriched rStSOD displays a great resistance; a moderate sensitivity is instead observed in the presence of a low Mn content. Contrary to hydrogen peroxide, sodium peroxynitrite is a powerful inactivator, a behaviour enhanced in the Mn-enriched enzyme. All these results were compared with the corresponding data previously reported for the cambialistic SOD from the taxonomically related S. mutans. In S. thermophilus the regulation of the enzyme functions by the Mn content appears less relevant with respect to S. mutans.
Keywords: enzyme regulation